Institutional capacity of health care institutes for diagnosis and management of common genetic diseases - A study from a north coastal district of Andhra Pradesh - Pagolu, Koteswara Rao; Rao, T Raghava (Journal of Community Medicine and Health Solutions, 2021)
Background: In India, the genetic disease is a disregarded service element in the community health- protection system. This study aims to gauge the accessibility of services for treating genetic disorders and also to evaluate the practices on deterrence and management services in the district health system. Methods: A cross-sectional survey of selected health amenities from 454 medical officers (MO’s), 94 accredited social health activist (ASHAs) workers, 86 multipurpose health assistant-female (MPHA-F), 34 multipurpose health assistant-male (MPHA-M), 14 multipurpose health supervisors-female (MPHS-F), 10 multipurpose health supervisors-male (MPHS-M), 6 multipurpose health extension officer/ community health officer (MPHEO/CHO), 10 public health nurse (PHN), 45 lab technicians (LT’s) working in the government health sector and 254 in the private health sector, 409 nursing staff working in the government health sector and 995 in the private health sector, 15 primary health centers (PHC’s), 4 community health centers (CHC’s), 1 district government hospital (DGH), 3 referral hospitals (RH’s). From the side of private health institutions 25 corporate hospitals (CH’s), 3 medical colleges (MC’s), and 25 diagnostic laboratories (DL’s) were conducted. Results: The findings show that adequate staff was in place at more than 70% of health centers, but none of the staff have obtained any operative training on genetic disease management. The largest part of the DH’s had rudimentary infrastructural and diagnostic facilities. However, the greater part of the CHC’s and PHC’s had inadequate diagnostic facilities related to genetic disease management. Biochemical, molecular, and cytogenetic services were not available at PHC’s and CHC’s. DH’s, RH’s, and all selected medical colleges were found to have offered the basic Biochemical genetics units during the survey. In 24% of CH’s, the basic biochemical units are available and 32% (8 out of 25) of DL’s have the advanced biochemical genetics units by study. Molecular genetics units were found to be available in 28% (7 out of 25) of DL’s during the study. About 6 (24%) diagnostic centers of cytogenetic laboratories were located in the Visakhapatnam district under the private sector. Conclusion: The district health care infrastructure in India has a shortage of basic services to be provided for the genetic disorder. With some policy resolutions and facility strengthening, it is possible to provide advanced services for a genetic disorder in the district health system.